Understanding the Impact of Information Literacy Instruction: A Multi-Method Approach - Gross, Melissa; Latham, Don (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This presentation summarizes the formal evaluation of an intervention developed for students who test as below proficient in information literacy. Findings demonstrate that the intervention can improve skills, but that the recalibration of self-views of ability and the attainment of competence is a complex problem that may require multiple interventions to be fully achieved. Cette communication résume l’évaluation formelle d’une intervention conçue pour les étudiants qui font preuve d’un manque de compétence informationnelle. Les résultats démontrent que l’intervention peut améliorer les compétences, mais que la recalibration de l’autoperception de la capacité et l’atteinte des compétences est un problème complexe qui nécessite de multiples interventions pour être pleinement corrigé.